The faces of war. The “Piedades” of Beatriz González. (2008)
More than two decades ago, the capture of the Palace of Justice by the armed group M-19, as well as its subsequent recovery by the Colombian military forces, left a balance of two hundred people dead, among subversives, Supreme Court Magistrates of Justic